The Effect Of Entrepreneurs' Financial Literacy And Managerial Competency On Msme Performance Moderated Education Level - Sari Wulandari; Sudarno Sudarno; Muhammad Sabandi (UNIVED Press, 2024)
This study aims to determine (1) the influence of entrepreneurs' financial literacy on the performance of Surakarta City MSMEs (2) the influence of entrepreneurs' managerial competence on the performance of Surakarta City MSMEs (3) find out whether the level of education can strengthen the influence of financial literacy and entrepreneurs' managerial competence. This type of research is quantitative with a population of 254 entrepreneurs in the city of Surakarta, obtaining a sample of 131 using convenience sampling techniques. Data collection techniques using a 1-5 point Likert scale questionnaire and dummy variables via Google Form. Data were processed using SPSS 25 software with instrument validity testing using Confirmatory Factor Analysis (CFA), reliability testing using Cronbach Alpha, hypothesis testing using Moderated Regression Analysis (MRA) with descriptive statistical tests and analysis prerequisite tests. The findings are (1) there is a significant and positive influence of entrepreneurs' financial literacy on the performance of MSMEs in Surakarta City. 2) there is a significant and positive influence of entrepreneurs' managerial competence on the performance of MSMEs in Surakarta City. (3) the level of education is not able to strengthen the literacy and managerial competence of entrepreneurs on the performance of MSMEs in the City of Surakarta. The implication is consistent with the Resourced Based View theory that financial literacy and managerial competence can improve the performance of MSMEs by attending seminars or training so that they can create new thinking to develop their businesses.